Cloning of α-L-arabinofuranosidase Genes and Its Expression in Escherichia coli: A Comparative Study of Recombinant Arabinofuranosidase Originatingin Bacillus subtilis DB104 and Newly Isolated Bacillus licheniformis CW1 - MOCHAMAD NURCHOLIS; NIKNIK NURHAYATI; IS HELIANTI; MARIA ULFAH; BUDIASIH WAHYUNTARI; AGUSTIN KRISNA WARDANI (Indonesian Society for microbiology, 2012)
Arabinofuranosidase (Abfa) is one of the most important enzymes involved in degradation of lignocelullose biomass. Two genes encoding α-L-Arabinofuranosidase (abfA), each from Bacillus subtilis DB104 (abfAa1) and an indigenous Indonesian B. licheniformis CW1 (abfAb3), were cloned by the PCR approach and expressed in Escherichia coli. Sequences analysis of abfAa1 and abfAb3 revealed that each consists of 1721 and 1739 base pairs long DNA, respectively. Each clone contains a hypothetical open reading frame of 1503 and 1509 bp that encode an Abfa protein of 500 and 502 amino acids for abfAa1 and abfAb3, respectively. The deduced amino acid sequence of AbfaB3 shares 75% identity to that of AbfaA1. The recombinant enzymes were expressed constitutively in E. coli. Partial characterization of those enzymes revealed that the AbfaA1 and AbfaB3 were optimally active at 50 ºC and 60 ºC at pH 6, respectively. Thermostability studies of the recombinant enzymes with p-nitrophenyl α-L-arabinofuranoside at their optimal conditions showed that up to 50% AbfaA1 activity was lost after 5 h incubation at 50 ºC, whereas the AbfaB3 retained its activity over 75% after 12 h pre-incubation oat 60 ºC. This thermostability study of recombinant AbfaB3 showed for the first time that the arabinofuranosidase from B. licheniformis is a thermostable enzyme. The recombinant enzyme showed a higher optimal reaction temperature (60 ºC) in comparison to the previously reported thermostable arabinofuranosidase. The thermostable AbfaB3 has a potential to be applied to the degradation of lignocellulose biomass synergistically with thermostable xylanases, for instance in the production of xylo-oligosaccharides.